An investigation of the management and leadership experiences of female school principals in the Ondangwa education regions - Udjombala, Maria (Rhodes University, Faculty of Education, Department of Education, 2002)
This study explores practical school leadership and management, as enacted by women. The study, conducted in an interpretive paradigm, attempts to gain an understanding of women's subjective experiences of school leadership and management. Two women principals from Ondangwa West Educational Region were interviewed. The two were selected through consultations with one of the senior inspectors in the region. Both had been principals for more than ten years and were seen by those who are concerned with their school to be successful. The study found that these women prefer a participative style of leadership and management, characterised by consultations with others, teamwork, collaborative decision-making and the use of power to empower others. They also strive for good human relationships because they believe that it fosters mutual respect, trust, openness and a good working atmosphere. All these human centred approaches are directed towards creating a school atmosphere that is conducive to teaching and learning and therefore result in effective schooling and quality educational outcomes. They do not experience gender discrimination in their work places. They have the full support of their supervisors. Though both are married with children, these dual roles do not prevent them from being successful in their professional work. In fact they have reached a stage where they feel confident as leaders and feel that they are acting as role models for fellow women principals and those aspiring to this position. The study concludes that the styles of leadership and management displayed by women are similar to those that are universally accepted as characteristics needed for effective school management and leadership. Though these leadership styles are traditionally associated with women, these characteristics are not gender specific. Therefore it will be in the best interest of schools, if school principals, both men and women, could borrow from these qualities in order to change schools from authoritarian to more democratic institutions.
Keywords: Women school principals -- Namibia -- Ondangwa; Educational leadership -- Namibia -- Ondangwa